Penerapan Model Pembelajaran TGT untuk Meningkatkan Motivasi Belajar pada Mata Pelajaran Caregiver - Purnama, Aldi Jaya; Tungga, Raphsodyan Sekar; Susilo, Heryanto (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
In order to create a pleasant learning atmosphere for students, teachers must plan learning in accordance with the characteristics of students. A pleasant learning atmosphere can support the process of developing the potential that exists in students, especially learning motivation. This study aims to determine the implementation of the Teams Games Tournament (TGT) learning model to increase students' learning motivation in class XI social work 3 SMKN 7 Surakarta. The research was conducted using the Classroom Action Research (PTK) method and data were obtained through questionnaires and classroom observations. The sample in this study were students in class XI social work 3 SMKN 7 Surakarta. Data analysis was carried out quantitatively to obtain information data from the results of a series of pre-test, post-test then the information was presented quantitatively descriptively. From the results of the study, it was found that before using the TGT model in the process of learning activities, students had very low learning motivation, but after proper treatment by implementing a learning design that had been adapted to the characteristics of students, students' learning motivation began to experience a significant increase.